Identification of a Novel UT-B Urea Transporter in Human Urothelial Cancer - Hou, Ruida; Alemozaffar, Mehrdad; Yang, Baoxue; Sands, Jeff M.; Kong, Xiangbo; Chen, Guangping (Frontiers in Physiology, 2017)
The urea transporter UT-B is widely expressed and has been studied in erythrocyte, kidney, brain and intestines. Interestingly, UT-B gene has been found more abundant in bladder than any other tissue. Recently, gene analyses demonstrate that SLC14A1 (UT-B) gene mutations are associated with bladder cancer, suggesting that urea transporter UT-B may play an important role in bladder carcinogenesis. In this study, we examined UT-B expression in bladder cancer with human primary bladder cancer tissues and cancer derived cell lines. Human UT-B has two isoforms. We found that normal bladder expresses long form of UT-B2 but was lost in 8 of 24 (33%) or significantly downregulated in 16 of 24 (67%) of primary bladder cancer patients. In contrast, the short form of UT-B1 lacking exon 3 was detected in 20 bladder cancer samples. Surprisingly, a 24-nt in-frame deletion in exon 4 in UT-B1 (UT-B1Δ24) was identified in 11 of 20 (55%) bladder tumors. This deletion caused a functional defect of UT-B1. Immunohistochemistry revealed that UT-B protein levels were significantly decreased in bladder cancers. Western blot analysis showed a weak UT-B band of 40 kDa in some tumors, consistent with UT-B1 gene expression detected by RT-PCR. Interestingly, bladder cancer associate UT-B1Δ24 was barely sialylated, reflecting impaired glycosylation of UT-B1 in bladder tumors. In conclusion, SLC14A1 gene and UT-B protein expression are significantly changed in bladder cancers. The aberrant UT-B expression may promote bladder cancer development or facilitate carcinogenesis induced by other carcinogens.